International Corporate Tax Avoidance Practices: Evidence from Australian Firms - Taylor, Grantley; Richardson, G. (Pergamon, 2012)
This paper examines the international corporate tax avoidance practices of publicly listed Australian firms. Based on a hand-collected sample of 203 publicly listed Australian firms over the 2006–2009 period (812 firm-years), our regression results indicate that there are several practices Australian firms use to aggressively reduce their tax liabilities. Specifically, we find that thin capitalization, transfer pricing, income shifting, multinationality, and tax haven utilization are significantly associated with tax avoidance. In fact, based on the magnitude and significance levels of the regression coefficients in our study, thin capitalization and transfer pricing represent the primary drivers of tax avoidance, whereas income shifting and tax haven utilization are less important. Finally, our additional regression results show that tax havens are likely to be used together with thin capitalization and transfer pricing to maximize international tax avoidance opportunities via the increased complexity of transactions carried out through tax havens.